Difficult Dialogues in the South: Questions about Practice - Nakata, Martin (The Australian Journal of Indigenous Education, 2017)
This is a reflective opinion piece, on our efforts in Australia to achieve alignment between the goals of Indigenous self-determination, Indigenous studies programmes and decolonising theory for an open and critical dialogue in south–south scholarship agendas. In this spirit, extant approaches to Indigenous studies in the Australian higher education context are questioned, the scholarship recruited for this is challenged, and its advocated role in the education of all students is raised as a major concern.